Kinetic Inductance Detectors For Future Observations of the Cosmic Microwave Background - LeFebre, Ryan William (Proceedings of the Wisconsin Space Conference, 2019)
Kinetic inductance detectors (KIDs) have a lot of potential in the field of astronomical observations; they are easy to fabricate and are highly multiplexible. KIDs can be as simple as a single lithographic layer and 1000s of them can be read out on a single line. Future observations of the cosmic microwave background (CMB) will require huge pixel count detector arrays and KIDs are able to fill this role promisingly. This paper primarily discusses the design and simulation of KIDs in Sonnet to be used in a polarimeter chip intended for observation of the polarization anisotropy of the CMB. Both background information of the CMB and KID theory will be reviewed.